Custos nas organizações públicas de saúde: uma proposta de alocação aos centros de custo na Unidade Saúde Escola da Universidade Federal de São Carlos - Ribeiro, Bruna Angélica Casonato (2020)
In view of the current scenario of public health in Brazil, there is an increase in health costs, largely due to the increase in life expectancy and the advancement of technology, contrasting with often insufficient and limited resources. Given this reality, accurately estimating costs is paramount in the search for efficiency and transparency. The identification and allocation of costs to their respective cost centers are of great relevance to managers, who can view the organization's ability to meet the demand presented. This study aimed to map and classify the costs of the Health School Unit (USE) of the Federal University of São Carlos (UFSCar) to the productive, administrative and intermediate cost centers, as directed by the Ministry of Health. The study can be classified as to the objective as exploratory in the form of a case study. As for the approach, qualitative research was carried out, with data collection, application of interviews, document analysis. The research involved surveying costs at the Unit from January 2018 to December 2019, segregating direct and indirect costs, determining cost centers, allocating costs to administrative, productive and intermediate cost centers, followed by direct allocation of costs to the final productive cost centers. Finally, an analysis of the information obtained was performed. It was found that the cost with the highest representation in percentage terms in the Unit was that of personnel, representing 80% in 2018 and 79% in 2019 of the Unit's total costs, followed by costs with third party services and legal entities with 16% in 2018 and 18% in 2019. Costs with consumables, on the other hand, have little representation in percentage terms, being 1.15 % in 2018 and 0.86% in 2019. Depreciation costs correspond to 2% of the Unit's total costs in 2018 and 3% of costs in 2019. The cost per procedure is higher for months with less number of visits and less with the highest number of services, since the organization has mostly fixed costs. The productive cost center had the highest cost in the years 2018 and 2019, being 58% and 56%, respectively, followed by the intermediate cost center with 23% in 2018 and 21% in 2019. Finally, the cost center administrative represented 18% in 2018 and 21% in 2019. As for the final productive cost centers, the one with the highest cost was Physiotherapy and the one with the lowest cost was Family Medicine in 2018 and General Medicine in 2019. The data presented demonstrate important subsidies for decision making, offering clear managerial information regarding the allocation of costs in the Unit, also allowing greater transparency of expenses.